Effect of Oxidative Stress on AhpC Activity and Virulence in katG Ser315 Thr Mycobacterium tuberculosis Mutant - Ning Rintiswati; Tri Wibawa; Widya Asmara; Hardyanto Soebono (Indonesian Journal of Biotechnology, 2011)
Mycobacterium tuberculosis strains resistance to INH is mainly caused by the alteration in several genesencoding the molecular targets. Mutation of katG at codon 315 especially Ser315Thr are responsible forINH resistance in a large proportion of TB cases. The aim of this study is to evaluate the influence of stressoxidative on AhpC activity of katG Ser315Thr of M.tuberculosis, and to find out the relation of AhpC and thevirulence of this mutant. The study design was laboratoric experimental, subjects of study were M.tuberculosisINH resistance strains, and the treatment were serial dose of H2O2. Eighty five M.tuberculosis INH resistantclinical strain were screened for mutation of katGSer315Thr by PCR/RFLP and characterized on the basis ofphenotypic properties (catalase activity and AhpC activity). AhpC activity of katG Ser315Thr M.tuberculosisstrains in response to oxidative stress condition was evaluated by culturing the strains on liquid culturemedium containing 1mM H2O2.To ascertain role of AhpC in the virulence of katGSer315Thr mutant strains, themutants were infected into human macrophages culture, and several indicator of virulence were observed (i.e:replication competence, and apoptosis induction on human macrophages). The results showed that katG Ser315Thr were identified in 23 (27,05%) of 85 INH resistance strains, all mutant strains had decrease of catalaseactivity. AhpC activity of katG Ser315Thr of M.tuberculosis increased significantly with increase of hydrogenperoxide dose. In addition , it has been shown that increased AhpC activity related to replication ability ofmutant, and reduction of apoptosis macrophages induction significantly. We conclude that the productionof AhpC of katG Ser315Thr M.tuberculosis induced by oxidative stress. There was a role of AhpC in virulenceof the M.tuberculosis katG Ser315Thr strains by replication capability and macrophages apoptosis.